The Effect of Jigsaw Type Cooperative Learning Strategy to Improve Students' Critical Thinking Patterns - Bunga Aprili; Chairunnisa Amelia (Berpusi Publishing, 2022)
The purpose of this study was to determine the effect of the jigsaw type cooperative learning strategy on students' thinking skills and to determine the thinking skills of sixth graders at SD Bina Taruna I. The type of research applied was quantitative research using the